The Pearl Sister : CeCe's Story - Riley, Lucinda (London Pan books, 2017)
"From the breathtaking beaches of Thailand to the barely tamed wilds of colonial Australia, The Pearl Sister is the next captivating story in New York Times bestselling author Lucinda Riley's epic series about two women searching for a place to call home. CeCe D'Apliese has always felt like an outcast. But following the death of her father--the reclusive billionaire affectionately called Pa Salt by the six daughters he adopted from around the globe--she finds herself more alone than ever. With nothing left to lose, CeCe delves into the mystery of her familial origins. The only clues she holds are a black and white photograph and the name of a female pioneer who once traversed the globe from Scotland to Australia. One hundred years earlier, Kitty McBride, a clergyman's daughter, abandoned her conservative upbringing to serve as the companion to a wealthy woman traveling from Edinburgh to Adelaide. Her ticket to a new land brings the adventure she dreamed of
Keywords: Australia -- Families -- Adopted children